Facilities Development with Training of Instructors in Maintenance and Display Case Repair in the Work Training Center (BLK) of Kuningan District - Triaji PP; Rizki Muliawan; Apip Badarudin; AR Lukitobudi; AP Edi S (LPPM UIKA Bogor, 2022)
The Kuningan West Java Vocational Training Center (BLK) is ready to create manpower to fill the world of work or independent businesses, to reduce unemployment rates. The condition of work training centers that have new buildings but are not yet supported with adequate equipment and human resources and according to needs still require support from stakeholders to improve their quality. Bandung State Polytechnic, especially the Department of Refrigeration and Air Conditioning Engineering, is experienced enough and feels the need to contribute to the development program of the BLK Kuningan, especially in the field of Facilities Development and Instructor Training in the Field of Maintenance and Repair of Display Cases at BLK Kuningan Regency. This program aims to increase the role of the BLK in increasing the competence of Human Resources according to the needs of the labor market. The method implemented is through the Facility Development and Instructor Training Program in the Field of Maintenance and Repair of Display Cases. This activity has been carried out in theory and practice with a ratio of 20% theory and 80% practice in the field which was held at BLK Kuningan. The outputs that have been achieved include training participants having sufficient competence as instructors in the field of refrigeration and air conditioning engineering, especially regarding maintenance and repair of display case machines, availability of job sheets and theory and practice modules on basic refrigeration, especially for display case machines, a set training unit display case and its service equipment.